Cloning and sequencing analysis of whole Spiroplasma genome in yeast - Mizutani, Masaki; Omori, Sawako; Yamane, Noriko; Suzuki, Yo; Glass, John I.; Chuang, Ray-Yuan; Fukatsu, Takema; Kakizawa, Shigeyuki (Frontiers in Microbiology, 2024)
Cloning and transfer of long-stranded DNA in the size of a bacterial whole genome has become possible by recent advancements in synthetic biology. For the whole genome cloning and whole genome transplantation, bacteria with small genomes have been mainly used, such as mycoplasmas and related species. The key benefits of whole genome cloning include the effective maintenance and preservation of an organism's complete genome within a yeast host, the capability to modify these genome sequences through yeast-based genetic engineering systems, and the subsequent use of these cloned genomes for further experiments. This approach provides a versatile platform for in-depth genomic studies and applications in synthetic biology. Here, we cloned an entire genome of an insect-associated bacterium, Spiroplasma chrysopicola, in yeast. The 1.12 Mbp whole genome was successfully cloned in yeast, and sequences of several clones were confirmed by Illumina sequencing. The cloning efficiency was high, and the clones contained only a few mutations, averaging 1.2 nucleotides per clone with a mutation rate of 4 ×10 -6 . The cloned genomes could be distributed and used for further research. This study serves as an initial step in the synthetic biology approach to Spiroplasma.